Perspektif Perawat Tentang Manejemen Terpadu Balita Sakit di Puskesmas Wilayah Kabupaten Bantul Yogyakarta - Ferika Indarwati (IJNP (Indonesian Journal of Nursing Practices), 2015)
Integrated Management of Childhood Illness (IMCI) is an integrated approach to the treatment of sick children in primary helath care services which include promotive, preventive and curative programs. The role of nurses in providing nursing care must be in accordance with the system of the health care centers. The purpose of this study was to determine Nurses Perspective on Integrated Management of Childhood Illness (IMCI) in Primary Health Care Centres, Bantul, Yogyakarta. The method used in this research is descriptive qualitative. The sampling was recruited by purposive sampling, 6 respondents was involved in this research. Data analysis was done by thematic analysis. The results of this study found that 5 out of 6 respondents can explain IMCI defi nition, objectives and actions of nurses that had been taken in IMCI. Respondents said that the biggest obstacle in implementing IMCI at health centers is the time, facilities and infrastructures. Sources like fi nancial support and the support of the leadership is very important to support the implementation of IMCI in health centers. Based on this research can be concluded that the implementation of IMCI in PHC requires the commitment of all parties, not only nurses but also doctors, health center leaders and other health workers. Advice can be given to Primary Health Care Centres associated with IMCI is conducting training for nurses, repair facilities and infrastructure so that implementation of IMCI in health centers could have better.Keywords: Nurse, Knowledge Level, IMCI, Health Center